The study of the antagonistic and growth-stimulating characteristics of Bacillus subtilis strains, promising for the development of the effective biofungicides - A. M. Asaturova; T. M. Sidorova; N. S. Tomashevich; N. A. Zhevnova; A. I. Khomyak; A. E. Kozitsyn; V. M. Dubyaga; M. D. Pavlova; N. M. Sidorov; V. V. Allakhverdyan (Аграрная наука Евро-Северо-Востока, 2020)
In the period from 2012 to 2015 on Kalym winter wheat variety plants there were carried out field tests of the liquid culture of B. subtilis BZR 336g and BZR 517 strains isolated from natural sources that exhibit antifungal activity against phytopathogenic fungi Fusarium graminearum, F. culmorum, Microdochium nivale and Pyrenophora tritici-repentis, and are also able to have a positive effect on the growth and development of plants. Pre-sowing seed treatment and two preventive treatments during the growing season of the plants were carried out with the liquid culture of the strains. Comparison variants - treatment with water (control), with chemical (Raxil, KS; Alto Super, KS) and with biological (Fitosporin-M, L) standards. Biological efficacy against the complex of fusarium root rots was noted in the shooting stage of winter wheat and during ripening, and in some years reached 22.8 % for B. subtilis BZR 336g strain and 17.2 % for B. subtilis BZR 517 strain. In variants with presowing seed treatment and treatment of vegetative winter wheat plants with B. subtilis BZR 336g strain for three years of field trials the yield was from 5.0 to 7.4 t / ha, and when treated with B. subtilis BZR 517 strain - from 4.2 to 7.6 t / ha. The maximum additional yield was obtained in 2013 - a reliable yield increase was 1.6 t / ha for B. subtilis BZR 336g strain and 0.8 t / ha for B. subtilis BZR 517 strain. The ability of liquid cultures of the studied strains to protect winter wheat against harmful diseases at the same level and above the biological and chemical standards will help to expand the range of microbial biological products in the segment of the Russian market of environmentally friendly plant protection products.